Effect of yeast mannan treatments on ripening progress and modification of cell wall polysaccharides in tomato fruit. (1st March 2017) - Xie, Fang; Yuan, Shuzhi; Pan, Hanxu; Wang, Rui; Cao, Jiankang; Jiang, Weibo
Highlights: Postharvest yeast mannan treatments delayed ripening progress of tomato fruit. Yeast mannan may act via suppression of ethylene synthesis of tomato in storage. Yeast mannan inhibited the modification of cell wall polysaccharides of tomato. Yeast mannan maintained the integrity of cell wall architecture of tomato fruit. Abstract: Yeast mannan treatments effectively delayed colour change and firmness decline and inhibited ethylene production in two cultivars of tomato fruit during storage. The yeast mannan treatment maintained the integrity of tomato pericarp cell wall architecture and suppressed the modification of water-soluble and insoluble pectic polysaccharides in the cell wall. A decrease in the neutral sugars, includingd -galactose, l -arabinose andl -rhamnose, in water-insoluble pectin and an increase in these sugars in water-soluble pectin were inhibited by yeast mannan. The contents ofd -xylose andd -mannose in the hemicellulose fraction were significantly higher in the yeast mannan-treated fruit after storage. The activities of several cell wall-modifying enzymes, including pectinmethylesterase, polygalacturonase and β-galactosidase, were suppressed in fruit treated with yeast mannan during storage. Overall, the yeast mannan-induced delay in the ripening progress of tomato fruit might occur via the strong suppression of ethylene synthesis, causing inhibition of solubilization and depolymerization of cell wall polysaccharides.